Surgical outcomes related to invasive EEG monitoring with subdural grids or depth electrodes in epilepsy patients - Chandensang, Prompong; Bunyaratavej, Krishnapundha (Thai Journal of Neurological Surgery, 2025)
Objectives: In drug-resistant epilepsy patients, who have uncertain epileptogenic foci from noninvasive investigation, resective surgery based on an invasive EEG-monitors performed with subdural grids (SDG) or depth electrodes/stereo-electroencephalography (DE/SEEG) is considered to be the best option towards achieving seizure-free state. Due to lack of such a study focusing on surgical outcomes in Thailand, the authors present those outcomes for comparison to other studies. Methods: The authors collected data of patients who underwent invasive EEG monitoring from the database of King Chulalongkorn Memorial Hospital (KCMH) between May 2012 to May 2022. We collected basic characteristics, past history, present illness, treatment history, intraoperative findings, complication and seizure outcomes. Then, we compare our results to the other studies. Results: Thirty patients were included. Eight patients (26.7%) underwent only SDG, 9 patients (30.0%) underwent only DE/SEEG, and 13 patients (43.3%) underwent both SDG and DE/SEEG. Engel I outcome was found in 23 patients (76.7%) and complications were found in 4 patients (13.3%). Conclusion: Invasive EEG monitoring surgery in KCMH had good outcomes in seizure control and low complication rate. Furthermore, this result was similar to other studies.